2016
DOI: 10.1186/s40643-016-0101-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methyl jasmonate and salycilic acid synergism on enhancement of bilobalide and ginkgolide production by immobilized cell cultures of Ginkgo biloba

Abstract: Background: Bilobalide and ginkgolides are reported to be present only in Ginkgo biloba. However, only trace amounts of bilobalide and ginkgolides are contained in the ginkgo leaves. Nowadays, there has been considerable interest in plant cell cultures as a potential alternative to traditional agriculture for the industrial production of secondary metabolites. Much effort has been put into the use of in vitro cultures as one attractive biotechnological strategy for producing bilobalide and ginkgolides of comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Similarly, it has been reported that the exogenous treatment with both SA and JA can result in an antagonistic effect on the production of PC and antioxidants in plants, because the salicylates can override aspects of JA signaling cascade [ 40 , 41 ]. However, antagonistic effect is not generalized and synergistic effect between SA and MeJA on plant secondary metabolism can also be produced [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it has been reported that the exogenous treatment with both SA and JA can result in an antagonistic effect on the production of PC and antioxidants in plants, because the salicylates can override aspects of JA signaling cascade [ 40 , 41 ]. However, antagonistic effect is not generalized and synergistic effect between SA and MeJA on plant secondary metabolism can also be produced [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the contents of TTLs in tissue cultures are much lower compared with the levels in leaves growing on G. biloba trees. Thus, JA-Me and salicylic acid have often been used to increase the biosynthesis of essential secondary metabolites [ 45 , 46 ]. These studies showed that the use of JA-Me in G. biloba cell culture increases TTLs but at the same time slightly decreases cell growth [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The applied JA-Me strongly increased the production of these metabolites in cells and stimulated their release into the culture medium. Sukito and Tachibana [ 46 ] showed that JA-Me elicitation in immobilized G. biloba cell cultures increases the production of TTLs, and synergism between JA-Me and salicylic acid was found. In our study, JA-Me increased the content of ginkgolides A, B, and C but not bilobalide ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have investigated G. biloba for the presence of different classes of chemical constituents, and the results revealed that this plant contains a number of secondary metabolites, including terpenoids, polyphenols, allyl phenols, organic acids, carbohydrates, fatty acids and lipids, amino acids, and inorganic salts [ 3 , 4 , 5 , 6 ]. Plant cell biotechnology studies on G. biloba focused on micropropagation or biosynthesis and accumulation of ginkgolides and bilobalide [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The other secondary metabolites, such as catechins, were rarely investigated in in vitro cultures [ 15 ].…”
Section: Introductionmentioning
confidence: 99%